Highly Reflective and Low Resistive Top Electrode for Organic Solar Cells and Modules by Low Temperature Silver Nanoparticle Ink - Tam, Kai Cheong; Saito, Hirotoshi; Maisch, Philipp; Forberich, Karen; Feroze, Sarmad; Hisaeda, Yutaka; Brabec, Christoph J.; Egelhaaf, Hans-Joachim (Solar RRL, 2021)
One of the issues that have caused a wide performance gap between commercially available organic photovoltaic (OPV) modules and the hero cells in literature lies in the lack of printable and roll-to-roll process compatible high-performance top electrodes. This work takes an unorthodox approach to this issue by developing a printable silver nanoparticle (AgNP) film top electrode that can achieve a similar performance as evaporated ones (EvapAg). It illustrates the developmental process from ink formulation to the critical processing conditions that are tailored for OPV devices procedurally. The resultant cells and modules with AgNP electrodes have achieved almost the same power conversion efficiencies (≈90%) as those with evaporated silver electrodes, as demonstrated for multiple material systems, printing methods, as well as layouts. Under low light condition, AgNP cells perform even significantly better than EvapAg ones, due to their lower leakage currents. More importantly, this work has demonstrated that fully printed OPV modules can achieve similar performance as small scale OPV cells with evaporated electrodes when both the electrical and optical performance of their top electrodes are comparable. With the latest generation of materials, this approach offers an attractive alternative for manufacturing of highly efficient OPV modules at large scale.
CRIS-Team Scopus Importer:2021-12-17
Keywords: inkjet printing; organic photovoltaics; organic solar modules; printed photovoltaics; silver nanoparticles; upscaling